NLRP3 inflammasome activation contributes to development of alopecia areata in C3H/HeJ mice. Issue 2 (26th July 2021) - Hashimoto, Kei; Yamada, Yoshihito; Sekiguchi, Kota; Mori, Sachi; Matsumoto, Tatsumi
Abstract: Alopecia areata (AA) is an autoimmune non‐scarring hair loss disease. Recently, several reports have suggested that innate immune systems such as interferon‐α (IFN‐α)‐producing plasmacytoid dendritic cells and NOD‐like receptor family pyrin domain‐containing protein 3 (NLRP3) inflammasomes play a role in the pathogenesis of AA. However, critical studies about their involvement in the initiation of AA have not yet been reported. Therefore, we investigated the expression of innate immune cytokines in serum and skin, and examined the effect of a selective NLRP3 inhibitor, MCC950, on AA in C3H/HeJ mice, induced by transferring cultured skin‐draining lymph node cells. IFN‐α production was upregulated in lesions of AA‐affected mice, and interleukin‐1β in serum and skin was highly expressed before onset as well as postonset. Furthermore, MCC950 treatment prevented AA development and promoted hair growth in AA mouse models by reducing NLRP3 signalling and Th1/Tc1 chemokines and cytokines in the skin. These results suggest that NLRP3 inflammasome contributes to AA onset and chronicity, and NLRP3 inhibitor may be a potential therapeutic agent for AA.